Comprehensive analysis of common mitochondrial DNA variants and colorectal cancer risk. - Webb, E; Broderick, P; Chandler, I; Lubbe, S; Penegar, S; Tomlinson, I; Houlston, R (2008)
Several lines of evidence implicate mitochondrial dysfunction in the development of cancer. To test the hypothesis that common mtDNA variation influences the risk of colorectal cancer (CRC), we genotyped 132 tagging mtDNA variants in a sample of 2854 CRC cases and 2822 controls. The variants examined capture approximately 80% of mtDNA common variation (excluding the hypervariable D-loop). We first tested for single marker associations; the strongest association detected was with A5657G (P=0.06). Overall the distribution of association P-values was consistent with a null distribution. Next, we classified individuals into the nine common European haplogroups and compared their distribution in cases and controls. This analysis also provided no evidence of an association between mitochondrial variation and CRC risk. In conclusion, our results provide little evidence that mitochondrial genetic background plays a role in modifying an individual's risk of developing CRC.